Residential construction plumbing - Shopware (Firm). (Bloomington, IL : Shopware Production, 2000)
Our Shown takes on plumbing as he works with a professional plumber. We find out what it takes to design the plumbing service, and how to install pipes, faucets, drains, sinks, bathtubs, and showers. Shawn shows us how to rough in the pipes, cut holes in the floor, sweat copper pipes, and bond PVC pipes.
DVD format.
Keywords: Plumbing